Bridging the generational gap between nurses and nurse managers: a qualitative study from Qatar - Ahmad A. Abujaber (14586054) (2024)
The nursing workforce comprises multiple generations, each with unique values, beliefs, and expectations that can influence communication, work ethic, and professional relationships. In Qatar, the generational gap between nurses and nurse managers poses challenges to effective communication and teamwork, impacting job satisfaction and patient outcomes. This study investigates the generational gap between nurses and nurse managers in Qatar, aiming to identify strategies to enhance collaboration and create a positive work environment. A qualitative research design was used, involving semi-structured interviews with 20 participants, including frontline nurses and senior nurse managers. Participants were purposively sampled to represent different generations. Data were collected through face-to-face and virtual interviews, then transcribed and thematically analyzed. Four key themes emerged: Optimizing the Work Environment: Older generations preferred transformational and situational leadership, while younger nurses valued respect, teamwork, accountability, and professionalism. Strengthening Work Atmosphere through Communication and values: Older nurses favored face-to-face communication, while younger nurses preferred digital tools. Cultivating Respect and Empathy: Younger nurses emphasized fairness in assignments and promotions, while older nurses focused on empathy and understanding. Dynamic Enhancement of Healthcare Systems: Younger nurses were more adaptable to technology and professional development, while older nurses prioritized clinical care and patient outcomes. The study reveals significant generational differences in leadership preferences, communication styles, and adaptability to technology. Addressing these gaps through effective leadership, ongoing education, and open communication can improve job satisfaction and patient care. Other Information Published in: BMC Nursing License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12912-024-02296-y